Faktor Risiko yang Berhubungan dengan Kasus Leptospirosis di Kota Yogyakarta Tahun 2011 - Iwan Himawan; Sarjito Eko Windarso; Muryoto Muryoto (Sanitasi: Jurnal Kesehatan Lingkungan, 2012)
Leptospirosis is a zoonosis disease which is suspectedly the most widely spread in the world, in-cluded Indonesia. In 2011, the number of leptospirosis case in Yogyakarta City was multi-folded compared with the previous years. The study was aimed to understand the factors correlated with the disease incidence in that city in 2011 by conducting an observational study with case control design. The number of sample both in case and control groups were 30. Cases were patients who are diagnosed with leptospirosis and recorded in case report of leptospirosis in the city’s health department in 2011. Meanwhile controls were a neighbor of patients who did not suffer the typical symptoms of leptospirosis. Data were obtained through interview and ob-servation. Data analysis was carried out in stages included univariate, bivariate and multivariate tests. The bivariate analysis showed that the following factors were correlated with leptospirosis: risky occupations (OR=6.000; 95 % CI=1.172-30.725, p=0.045), contact history with mice (OR= 5.231; 95 % CI=1.675-16.515, p=0.008), having history of wounds (OR=5,675; 95 % CI=1,841-17,494; p=0,004) and behavior of wearing personal protective equipment (OR=5,444; 95 % CI=1,804-16,427; p=0,005); The subsequent logistic regression test showed that only having his-tory of wounds and behavior of wearing personal protective equipment were significantly cor-related with leprospirosis. Overall, people with both conditions have probablity of getting the disease as much as 88,77 %.